Pengaruh Kejelasan Sasaran Anggaran, Partisipasi Penyusunan Anggaran, Akuntabilitas terhadap Kinerja Manajerial dan Kinerja Anggaran pada Dinas Perumahan Rakyat dan Kawasan Permukiman Kota Banjarmasin - Ramadhan, Muhammad (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This study aims to examine the Influence of Clarity of Budget Targets, Participation in Budget Preparation, Accountability on Managerial Performance and Budget Performance as intervening variables on employees of the Women's Empowerment and Child Protection Service of Banjarmasin City. The population in this study was 53 civil servants, data was taken from questionnaires distributed to respondents. Data were analyzed using SmartPLS Version 3. The results of this study are Clarity of budget targets affects Managerial performance, Participation in budget preparation affects managerial performance, Accountability affects managerial performance, Clarity of budget targets affects Budget performance, Participation in budget preparation affects Budget performance, Accountability affects Budget performance, Managerial performance affects budget performance, Managerial performance mediates the influence of clarity of budget targets on budget performance, Managerial performance mediates the influence of participation in budget preparation on budget performance, Managerial performance mediates the influence of accountability on budget performance at the Women's Empowerment and Child Protection Service of Banjarmasin City Keywords: Budget Targets, Participation, Budgeting, Accountability, Managerial Performance, Budget Performance